Identification of Training Needs of the Coconut Growers in Sri Lanka - Herath, Chaminda S. (International Coconut Community Journal, 2016)
The coconut farming sector in Sri Lanka has been facing many problems which eventually led to a decrease in production and profitability in coconut farming. The main reason for the decrease in production has been the non adoption of scientific technologies primarily due to the lack of technical knowledge of coconut growers on scientific cultivation practices. Hence, a study was undertaken to assess the technical knowledge and the level of adoption of management practices with a view to identify and prioritize the training needs of coconut growers’. Training needs of the growers were assessed using the Borich Needs Assessment Model. The identified training needs were filtered by quadrant analysis. The discrepancy score of grower’s and the coconut development officers’ of the three districts were used as the dimensions of the quadrant analysis. The training needs were identified under four categories namely, planting practices, fertilizer application practices, agronomy practices and pest management practices. The study revealed that the most knowledgeable aspect was the planting practices and the least knowledgeable was the pest management practices, as evidenced by higher level of adoption of planting practices and the least adoption of pest management practices. It was concluded from the study that the most desirable training need was on the pest management practices followed by fertilizer application practices in the coconut triangle of Sri Lanka.